The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1101/183939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What the structural-functional connectome reveals about brain aging: The key role of the fronto-striatal-thalamic circuit and the rejuvenating impact of physical activity

Abstract: Physiological ageing affects brain structure and function impacting its morphology, connectivity and performance. However, at which extent brain-connectivity metrics reflect the age of an individual and whether treatments or lifestyle factors such as physical activity influence the age-connectivity match is still unclear. Here, we assessed the level of physical activity and collected brain images from healthy participants (N=155) ranging from 10 to 80 years to build functional (resting-state) and structural (t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…One study also found that thalamic volume showed a significant correlation with age (Cherubini et al, 2009). Another study found that the structure–function connectivity between the thalamus and the orbitofrontal and frontal areas made a major contribution to age estimation, which played a key role in the process of healthy aging (Bonifazi et al, 2017). Hughes et al (2012) suggested that age primarily affected thalamic nuclei connecting to the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…One study also found that thalamic volume showed a significant correlation with age (Cherubini et al, 2009). Another study found that the structure–function connectivity between the thalamus and the orbitofrontal and frontal areas made a major contribution to age estimation, which played a key role in the process of healthy aging (Bonifazi et al, 2017). Hughes et al (2012) suggested that age primarily affected thalamic nuclei connecting to the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evaluated brain processing of cognitive functions including memory speed, decision-making, attention, and perception during aging using functional magnetic resonance imaging (Branch et al, 2019;Löckenhoff & Rutt, 2017;Löckenhoff et al, 2020;Tausen et al, 2020). These and other morphological studies indicate structural modifications such as decrease of synapse and spine densities, decrease in grey matter and volume as well as microcolumn disorganization in cognitive regions of the brain (Alexander et al, 2020;Bonifazi et al, 2018;Guerra-Gomes et al, 2018;Peters & Kemper, 2012). However, very few studies have addressed the ultrastructural changes occurring during aging.…”
Section: Introductionmentioning
confidence: 99%